Financial Distress Analysis of The Sminfra18 Index Share Return on Indonesia Stock Exchange - Yuliandi Yuliandi; Hendro Sasongko; Dedi Budiman Hakim (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2021)
The construction sector in Indonesia has a strategic contribution to the national economy. This can be seen clearly by the increasing development of office buildings, hotels, apartments and malls as well as road construction projects, toll roads, flyovers, and so on, this will have an impact on improving Indonesia's infrastructure. Along with the increase in market capitalization on the SMinfra18 Index, it becomes ironic when it is not accompanied by the performance, volume and value of the SMinfra18 Index which is still volatile. It is feared that this will lead to financial distress as a result of the Global Financial Crisis, so that many companies cannot fulfill their obligations to banks. Basically, financial distress becomes an interesting thing that business stakeholders need to know, especially management and investors. For management to be able to manage and maintain business performance, while for investors as an indicator of investment activities. The purpose of the study is related to 1) The condition of the financial performance of companies listed in SMInfra18. 2) Factors that affect SMInfra18 financial distress and 3) The relationship between financial distress and stock returns in SMInfra18. The analysis method used is panel data regression using Debt Service Coverage Ratio, Profitability Ratio (ROE), Liquidity Ratio (WC / TA), Activity Ratio (TATO), Efficiency Ratio (EBITDA / TA) and Leverage Ratio (DAR). The results provide an illustration that there are differences and financial distress conditions in each company and the grouping and conditions of financial distress and stock returns have not been able to have a unidirectional relationship from time to time.